DISTRIBUTION OF FISH FAUNA IN THE SPRING FED STREAMS OF UTTARAKHAND - NAUTIYAL, PRAKASH; MISHRA, ASHEESH SHIVAM (Journal of the Inland Fisheries Society of India, 2021)
Altitudinal variation in fish abundance was investigated in the spring-fed streams of the mid and lower mountain areas and Doon Valley of Uttarakhand. In the ‘upper reaches’ of mid-mountain area (1400-850m asl), Shizothorax richardsonii was dominant at 1370 m and Shizothorax plagiostomus at 850 m asl. In the ‘lower reaches’ of mid-mountain area (1600- 700 m asl) Neolissochilus chelynoides and Barilius bendelisis prevailed in equal proportions at 1800 m while Schistura rupecola was abundant at 1600 m asl. B. bendelisis was dominant in the 700-800 m range. In the‘upper reaches’ of lower-mountain area and terai (1000-300 m asl) S. richardsonii was dominant at 1000 m asl while B. bendelisis from 1100-1000 m. In the ‘lower reaches’ of lower-mountain area Tor putitora was abundant around 500 m asl in veryselective streams and Gara gotyla at 355 m. Channa punctatus and Tor tor dominated at 245 m in the Sharda. In the Doon Valley Barilius vagra and Puntius conchonius were abundant only in some streams of the Doon Valley from 600 to 300 m asl. B. bendelisis was largely abundant in most of the streams of the Doon valley and predominant in some; the Song at Chhidderwala (43%), Shyampur Khadri (51%), Burhi Tons at both Guchupani (49%) and Tapkeshwar (74%) and in the Asan at Dharmawala (72%). Longitudinal variation in faunal abundance was also observed in the Gomti, Kosi and Doon valley streams; the Song (B. vagra at Doiwala, while Puntius conchonius and B. bendelisis downstream at Chhidderwala) and the Asan (P. ticto and B. bendelisis) However, in the Burhi Tons no longitudinal variation occurred as B. bendelisis was abundant species at both Guchupani and Tapkeshwar.Key words: Lesser Himalaya, Doon valley, altitude, Schistura sp., Schizothorax sp., Barilius sp